Analysis of Multistability of Financial Risk Chaos Systems and Its Application to Voice Cryptography - Yuningsih, SIti Hadiaty; Hidayana, Rizki Apriva; Nurkholipah, Nenden Siti (Research Collaboration Community (Rescollacom), 2024)
In the chaos literature, the application of modeling and control of dynamic systems in chaos theory arising in several fields is investigated. In this article we analyze complex financial chaos systems with countries as interest rates, investment demand, and price indices. The proposed chaotic flow's dynamic behavior is examined using phase portraits, eigenvalues, bifurcation diagrams, and Lyapunov exponent spectra. A significant quantity of research on secure communication systems has been published in recent years as a result of the major advancements in communications equipment and encryption techniques. A new voice encryption algorithm design is given using a financial chaos model. An application for voice encryption is conducted using the suggested algorithm, and the outcomes are described.